Canadian Bijuralism and the Concept of an Acquisition of Property in the Federal Income Tax Act - Duff, David (McGill Law Journal / Revue de droit de McGill, 2009)
AbstractThe acquisition of property plays an important role in the federal Income Tax Act (ITA), determining eligibility for a number of tax benefits, including entitlement to capital cost allowance, investment tax credits, and the deductibility of interest expenses incurred in respect of eligible property. In spite of its importance, the concept of an acquisition of property is not defined in the ITA, and it has been subject to divergent interpretations in the common law and the civil law.The author traces the sources of law informing the meaning of an acquisition of property in the common law and the civil law, and concludes that certain transactions may be subject to different tax consequences depending on whether they occurred in a common law province or in Quebec. The author demonstrates that the primary reference for determining whether a taxpayer acquired property—the twofold test in M.N.R. v. Wardean Drilling Ltd.—is premised on common law concepts and is incompatible with the goals of Canadian bijuralism expressed in the Federal Law—Civil Law Harmonization Act, No. 1 and section 8.1 of the federal Interpretation Act. In response to this contradiction, the author proposes a number of statutory amendments to ensure the uniform and predictable application of the ITA across Canada.